Parental knowledge of concussion: Evaluation of the CDC's "Heads up to parents" educational initiative. (June 2019) - Rice, Tracy; Curtis, Reagan
Abstract: Background : Potential negative outcomes associated with sport-related concussion drive the need for resources to educate parents about prevention, recognition, and management of concussion in the youth athlete. Parents play a critical role in the recognition and management of concussion for their child. Purpose : This study aims to (a) investigate current knowledge of concussion among parents whose children age 5–18 years play a club sport and (b) identify effects of an online video versus online print educational intervention on concussion knowledge change and learning. Methods: 140 parents whose children played a club sport answered questions regarding their knowledge of sport-related concussion pre- and post-random assignment to an educational intervention: CDC Concussion Awareness video or CDC Concussion Fact Sheet for Parents. Results : Participating parents demonstrated a moderate level of pre-intervention knowledge, but critical gaps in knowledge were identified. Knowledge of concussion improved slightly following intervention regardless of intervention type. Conclusions : This study confirms the presence of gaps in knowledge of concussion in parents whose children play club sports. Without the protection of concussion legislation, those athletes who participate in club sports are at particular risk due to lack of concussion knowledge and education. This study confirms that education can have a positive impact on parental knowledge of concussion. Practical applications: Pre-knowledge of concussion is the greatest predictor of post-knowledge of concussion, therefore pre-assessment of target audience knowledge followed by a custom educational intervention taking into account principles of adult learning, would be the most beneficial to increasing concussion knowledge. Highlights: Critical gaps in knowledge of concussion exists in parents whose children play club sports. Without the protection of concussion legislation, those athletes who participate in club sports are at particular risk due to lack of concussion knowledge and education. Education can have a positive impact on parental knowledge of concussion. Pre-knowledge of concussion is the greatest predictor of post-knowledge of concussion. Pre-assessment of target audience knowledge followed by a custom educational intervention taking into account principles of adult learning may be the best way to increase parental concussion knowledge. Concussion Interventions should utilize teaching strategies targeted to adult learners and allow time for reflection and discussion to facilitate assimilation of new information.